Chocolate e mel: negritude, antirracismo e controvérsia nas músicas de Gilberto Gil (1972-1985) - Nacked, Rafaela Capelossa (2015)
This research aims to investigate the poetics of blackness and this anti-racism in the lyrics of Gilberto Gil songs recorded between 1972 and 1985. The focus of this research explores the political dimension of Gil songs, his role as political and artistic militancy at Movimento Negro Unificado, the Blocos afro-carnavalescos from Salvador, afoxé Filhos de Gandhy and Candomblé, articulating artistic subjectivity, artistic work as well as the racial identity politics that were at stake in this effervescent historic moment throughout the Black Atlantic. Its purpose is to contribute to cultural studies and representations, supporting studies and actions based on the role of music in subjectivity and emancipation historically racialized populations